# how to remove equation label in subequation?

I have the following commands to create 2 lines of equation. The first line contains 4 equations therefore it should be labeled as (1a-d). The second line contains 2 equations therefore it should be labeled as (1f-e). But since subequation has automatic labeling it ruins everything.

{\begin{subequations}\label{eq:1}
$$\refstepcounter{equation}\tag{\theequation a-d}\ \bar{\eta}_1(\frac{\mathcal{L}}{2}) = \bar{\eta}_3(0), \qquad \frac{\partial \bar{\eta}_1}{\partial X}(\frac{\mathcal{L}}{2}) = \frac{\partial \bar{\eta}_3}{\partial X}(0), \qquad \eta(\frac{\mathcal{L}}{2})=0,$$
$$\refstepcounter{equation}\tag{\theequation e-f}\ \qquad \eta(0) = \bar{\eta}_1(0) = \frac{1}{2}. \bar{\eta}_3(\infty)=0.$$
\end{subequations}}


Use \ref:

\documentclass{article}
\usepackage{amsmath}

\newcommand{\pder}[2]{\frac{\partial #1}{\partial #2}}

\begin{document}

Here are six equations grouped in a fancy way
\begin{subequations}\label{double}
\begin{gather}
\eta\Bigl(\frac{\mathcal{L}}{2}\Bigr)=0,
\tag{\ref{double}a--c}
\\
$$0=0$$